Concerted Structural analysis predictions of an organohalide pollutants uptake enzyme, putative permease protein (DehHsAADcPt) from Halomonas smyrnensis AAD6T.: Comparative Structural Prediction of putative permease protein (DehHsAADcPt) - Oyewusi, Habeebat Adekilekun; Oladipo, Oluwatosin; Adekilekun, Habeebulahi; Abdul Wahab, Roswanira; Akinyede, Kolajo; Oladimeji Tugbobo, Samuel; Wayan Gunam, Ida Bagus; Huyop, Fahrul (Journal of Tropical Life Science, 2026)
Halomonas smyrnensis AAD6T is a halophilic bacterium capable of utilizing haloalkanoic acid and possessing a specific gene for the uptake of organohalide pollutants. This distinctive characteristic has garnered the attention of researchers who seek to understand the underlying mechanisms. Among its genome, a putative permease protein known as DehHsAADcPt has been identified as a potential candidate for facilitating the uptake of these pollutants. Structural predictions of DehHsAADcPt have been conducted to gain a better understanding of its potential role in pollutant uptake. The predictions of DehHsAADcPt's structural characteristics, presented in this study, shed light on its potential application in bioremediation efforts. The implications of these findings are discussed in detail. The in-silico characterization and functional analysis of DehHsAADcPt was carried out with different bio-computational tools or servers. DehHsAADcPt belongs to the ABC inner membrane transporter permease family protein that is highly basic, hydrophobic, and thermostable having a molecular weight of 58,885.47Da as revealed from ExPASy server. The DehHsAADcPt compost mostly alpha helix structure and functional motif belongs to the binding-protein-dependent transport system inner membrane components and phage shock protein family. The 3-D structure obtained by AlphaFold2 homology modeling program and verified by Ramachandran plot revealed that most of the residues are in the allowed or favored regions of the plot. Likewise, several amino acid residues are predicted as ligand binding residues and most of them are highly conserved. The different computational tools used have proven to give holistic structural analysis predictions of DehHsAADcPt and revealed the concerted nature of these tools in elucidation. This study provides valuable insights into the structural and functional properties of DehHsAADcPt protein, which could pave the way for its potential application in the bioremediation of halogenated organic pollutants.